The traveler's atlas, North America - Dailey, Donna (Apple, 2009)
This book takes you to 50 exceptional destinations in Canada, the United States, and Mexico, both on and off the beaten track. From the icy reaches of Prince Edward Island to the Mayan pyramids in the Yucatán, this guide describes the iconic landmarks, national parks, and man-made wonders along the way.